Bernoulli in the Operating Room: From the Perspective of a Cardiac Surgeon - Matt, Peter (The Thoracic and Cardiovascular Surgeon, 2014)
The Bernoullis were one of the most distinguished families in the history of science. It was Daniel Bernoulli who applied mathematical physics to medicine to further his understanding of physiological mechanisms that have an impact even in today's high-end medicine. His masterwork was the analysis of fluid dynamics, which resulted in Bernoulli's law. Most important for cardiac surgery, it describes how a centrifugal pump works within an extracorporeal circulation, lays the basis for measuring a gradient over a stenotic heart valve, and explains how to measure the transit time flow within a bypass graft.
Keywords: history; heart valve surgery; cardiopulmonary bypass